The Impact of Electronic Waste on human and environment health - Alabdali, Abdullah Ahmad (Journal of natural sciences, life and applied sciences, 2022)
This study aimed to identify electronic waste and the risks that might be caused to human beings and environmental health. It also aimed to recognize the sources and reasons behind the risks that may arise from electronic waste and the ways of their disposal. The study concluded with the following several results: 1. According to the point of view of the sample, the most important sources of e- waste are screens and keyboards, followed by mobile phone batteries in second place, while electronic circuit boards ranked third, and cell phones or mobiles came in fourth place. 2. E- waste contributes to many risks, the most important of which, is that e- waste contributes to a long- term defect in the brain, kidneys, and fetus, and also contributes to a disruption in the communication between cells in the event of exposure to low doses for long periods and to a high degree High. 3. The study results showed that there are many effective methods to protect against the dangers of e- waste. Also, this study concluded with the following recommendations: - To Include the importance of preserving the environment and the risks of environmental pollution originating from electronic waste in the curricula of the different educational stages in order to urge students to be aware of preserving the environment from the various sources of pollution. - To ensure the necessity of commitment of electronic devices importing and manufacturing companies to disclose the elements and chemicals contained in the devices intended for sale, which may cause risks to the environment and human health. - To Prepare research and technical studies to find appropriate solutions to reduce the phenomenon of electronic waste by devising ways to safely dispose of it to ward off environmental pollution and potential radiation that these electronic devices can emit.